Shaping globalization for poverty alleviation and food security - Díaz-Bonilla, Eugenio; Robinson, Sherman (International Food Policy Research Institute, 2001)
In its broadest sense, globalization can be seen as an inherent part of human experience. Since prehistoric times humans have been growing in number; interacting with other groups, peace-fully or not; building larger economic, social, and political organizations; discovering, using, and sometimes destroying the resources of the planet; and generating new knowledge and technologies. That process has led to the emergence of empires, with the ebb and flow over the centuries of explorers, crusaders, missionaries, merchants, and colonists. The powerful wave of globalization associated with modern